STUDY OF BLOOD COAGULATION PARAMETERS AND ACTIVITY INDICES IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Sagatova Dilnoza Rakhimovna; Ravshanova Shahnoza Farkhod qizi (Journal Park Publishing, 2025)
Objective. To evaluate the blood coagulation (hemostasis) indicators and disease activity indices in patients with systemic lupus erythematosus (SLE). Materials and methods. A total of 75 patients (73 women and 2 men) with SLE, who were under observation at the Rheumatology Center of the 1st Clinic of Tashkent Medical Academy, were involved in the study. The patients were diagnosed with SLE based on the criteria of the American College of Rheumatology (ACR), and the APS diagnosis was made according to the Sapporo criteria. SLE activity was evaluated based on SLAM, SLEDAI, and ECLAM indices. Results. In patients with SLE: Spontaneous platelet aggregation increased 5 times (p<0.01); the concentration of von Willebrand factor antigen (FV:Ag) increased more than 3 times; platelet activation was observed along with a 27% decrease in aggregation with collagen (p<0.01); a direct correlation was found between activity indices and the following indicators: RFMK (ECLAM, r=0.51), Fibrinogen (SLAM, r=0.34), D-dimer (ECLAM, r=0.5), Spontaneous platelet aggregation (ECLAM, r=0.5). AT III activity showed a negative correlation with SLEDAI: r = -0.73. Conclusion. Hemostasis system changes in SLE may indicate the development of thrombotic disorders in advance. At the same time, these indicators indicate the need for correction with medications. There is a direct relationship between the activity of the coagulation system and SLE activity indices.
Keywords: SLE, antithrombin III, D-dimer, activity indices, soluble fibrin-monomer complexes.